Longitudinal dynamics of hemostatic biomarkers in patients with cancer receiving immune checkpoint inhibitors vs chemotherapy: results from the Vienna CAT-BLED study - Nikola Vladic; Cornelia Englisch; Julia Maria Berger; Florian Moik; Hubert Hayden; Johannes Thaler; Anna Sophie Berghoff; Thorsten Fuereder; Matthias Preusser; Ingrid Pabinger; Cihan Ay (Research and Practice in Thrombosis and Haemostasis, 2025)
Background: Venous thromboembolism is a common cause of morbidity and mortality in patients with cancer, with chemotherapy being an established risk factor. Emerging data suggest elevated venous thromboembolism risk with immune checkpoint inhibitors (ICIs), yet the association between ICIs and hypercoagulability remains unclear. Objectives: We aimed to evaluate longitudinal levels of hemostatic biomarkers in patients during chemotherapy and ICI monotherapy. Methods: Patients were matched by age, sex, cancer type, and stage. Biomarker levels were measured at baseline, 3 weeks and 3 months after treatment and compared using Wilcoxon rank-sum tests with a mixed-effects model used to assess the effects of therapy and time. Spearman’s correlation analyzed biomarker relationships. Results: Thirty patients (20 with non–small cell lung cancer and 10 with head and neck cancer) were included. Eighteen patients (60%) were females, with a median age of 66 years (IQR, 57-78). Levels of soluble P-selectin, D-dimer, extracellular vesicle tissue factor activity, peak thrombin, and neutrophil extracellular trap formation (via citrullinated histone H3 in complex with extracellular DNA) showed an increasing tendency over time, with comparable biomarker levels between treatment modalities. Mixed-effects analysis revealed weak differences in the longitudinal dynamics of biomarker levels within the first 3 months of treatment, with ICI therapy (compared with chemotherapy) being associated with higher levels of soluble P-selectin (+3.03 ng/mL; P = .61), D-dimer (+0.01 mg/mL; P = .99), extracellular vesicle tissue factor activity (+0.05 pg/mL; P = .58), and citrullinated histone H3 in complex with extracellular DNA (+15.22 ng/mL; P = .06), and lower peak thrombin levels (−34.34 nM; P = .29). Conclusion: Hemostatic biomarker levels were largely comparable between the 2 treatment modalities and showed increasing trends over time.